2021
DOI: 10.3390/life11080840
|View full text |Cite
|
Sign up to set email alerts
|

Chemoembolization for Single Large Hepatocellular Carcinoma with Preserved Liver Function: Analysis of Factors Predicting Clinical Outcomes in a 302 Patient Cohort

Abstract: The purpose of this study was to define the role of transcatheter arterial chemoembolization (TACE) in patients with a single large hepatocellular carcinoma (HCC) and define the patient groups benefiting from TACE. Treatment-naïve patients with preserved liver function who received TACE as the first-line treatment for single large (> 5 cm) HCC without macrovascular invasion and extrahepatic metastasis between 2007 and 2019 were retrospectively analyzed. Overall survival, progression-free survival, radiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In a cohort of 302 patients, Kim et al concluded that the efficacy of TACE in treating a single large HCC (>10 cm) remains uncertain. 30 Due to compromised liver function, these patients typically exhibited a relatively high rate of major complications (21%). 30 Similarly, according to the EASL guidelines, large HCC (>10 cm) is considered a relative contraindication for TACE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cohort of 302 patients, Kim et al concluded that the efficacy of TACE in treating a single large HCC (>10 cm) remains uncertain. 30 Due to compromised liver function, these patients typically exhibited a relatively high rate of major complications (21%). 30 Similarly, according to the EASL guidelines, large HCC (>10 cm) is considered a relative contraindication for TACE.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Due to compromised liver function, these patients typically exhibited a relatively high rate of major complications (21%). 30 Similarly, according to the EASL guidelines, large HCC (>10 cm) is considered a relative contraindication for TACE. 31 Nevertheless, we found that the large HCC (>10 cm) was not a significant prognostic factor for survival after TACE.…”
Section: Discussionmentioning
confidence: 99%
“…In a 302 patient cohort, Kim et al concluded that the use of TACE for the treatment of single huge HCC (>10 cm) remains questionable. 28 Another study on 821 BCLC B patients treated with TACE, Kim et al proposed a new subclassification pushing the tumoral limits to the up to 11 criteria. 29 According to the survival results of the new B3 class (median survival 11.3 months), TACE is not recommended in this new class.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, evaluation of safety profiles showed that only large tumor size (>10 cm) was significantly associated with the occurrence of major complications, with a relatively high rate (21/98; 21%). TACE has been considered a relative contraindication for the treatment of huge HCC (> 10 cm) due to the increased risk of peri-procedural adverse effects and the suboptimal treatment response ( 33 , 34 ), and recent studies reported that hepatic arterial infusion chemotherapy (HAIC) was found to prolong OS compared with TACE in patients with huge HCC ( 35 37 ). A recent randomized phase III trial showed that the use of combinations of chemotherapy fluorouracil/leucovorin/oxaliplatin in HAIC group had a better OS (HR 0.57 [95% CI, 0.44 to 0.74]; P <.001) and a lower incidence of serious adverse events (19% vs. 30%, P = .03) compared with the TACE group for patients with large unresectable HCC without vascular invasion or extrahepatic metastasis ( 38 ).…”
Section: Discussionmentioning
confidence: 99%